2005
DOI: 10.1056/nejmoa050080
|View full text |Cite|
|
Sign up to set email alerts
|

Normal Fasting Plasma Glucose Levels and Type 2 Diabetes in Young Men

Abstract: Higher fasting plasma glucose levels within the normoglycemic range constitute an independent risk factor for type 2 diabetes among young men, and such levels may help, along with body-mass index and triglyceride levels, to identify apparently healthy men at increased risk for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
288
4
13

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(343 citation statements)
references
References 36 publications
33
288
4
13
Order By: Relevance
“…The reduction of the cut-off point of FPG from 6.1 to 5.6 recommended by ADA in 2003 has been widely debated, especially in those publications dealing with its merits in predicting future diabetes [10][11][12][13]. In the present study, we found a significantly higher risk of developing diabetes in non-diabetic subjects with FPG ranging from 5.6 to 6.0 mmol/l, compared with NGT subjects with FPG <5.6 mmol/l.…”
Section: Discussionmentioning
confidence: 40%
“…The reduction of the cut-off point of FPG from 6.1 to 5.6 recommended by ADA in 2003 has been widely debated, especially in those publications dealing with its merits in predicting future diabetes [10][11][12][13]. In the present study, we found a significantly higher risk of developing diabetes in non-diabetic subjects with FPG ranging from 5.6 to 6.0 mmol/l, compared with NGT subjects with FPG <5.6 mmol/l.…”
Section: Discussionmentioning
confidence: 40%
“…The results from the MELANY study showed that increased fasting glucose level, even within the normal range (o5.55 mmol l À1 ), constitute an independent risk factor for type 2 diabetes mellitus. 12 These results may suggest that there is a relative overproduction of hepatic glucose already existent in patients at risk of developing diabetes mellitus.…”
Section: Discussionmentioning
confidence: 98%
“…A low level of physical activity, abdominal obesity and presence of the metabolic syndrome also commonly confer an increased risk of T2D (11,12). In addition, an elevated glucose concentration per se is a strong predictor of future T2D (5,13). In a prospective study of 2,115 non-diabetic individuals followed for six years within the Botnia study we could show that individuals with a family-history of T2D, with a BMI  30 kg/m 2 , and fasting …”
Section: Prediction Of Future Type 2 Diabetesmentioning
confidence: 99%